Characterization of variability of epidemically active strains of measles virus circulating in the North-Eastern region of Ukraine - Kalinichenko , Svetlana; Melentyeva , Kristina; Toryanyk, Inna; Antusheva , Tatyana (Annals of Mechnikov’s Institute, 2022)
The incidence of measles, despite the availability of effective preventive measures, remains an urgent medical and social problem worldwide, which is included in the list of infections that in the long run can be reduced to isolated cases. Infectious morbidity of the population to some extent depends on the quality of preventive measures, among which specific prevention is the most successful, effective and cheap medical and preventive means. Genotyping of measles virus isolates circulating in a certain area is used to track the routes of measles virus transmission and to differentiate post-vaccination complications from cases of disease caused by infection with wild-type strains. Material & methods. WHO Molecular External Quality Assessment Program, WHO Centralized Infectious Diseases Information System EUR, WHO Measles Surveillance Databases. Statistical data and reporting forms on the conducted epidemiological, virological and serological studies on measles infection in the Kharkiv region for 2017-2020, provided by the State Institution "Kharkiv regional medical center of the Ministry of Health of Ukraine". Neighbor-Joining clustering method for the creation of phylogenetic trees and the MADx 10 program. Results & discussion. To determine the epidemiologically important variants of МV sequences in the North-Eastern region of Ukraine, we summarized data from MeaNS databases on the predominant strains called "named strains" of genotypes, namely D8 and B3, analyzing their phylogeny (N-450 nucleotides). We analyzed the genetic relationships and evolutionary distances between closely related strains of genotypes B3 and D8. To do this, using the latest version of MADx, which allows you to compare data from servers around the world, we built family trees of phylogenetic sequences of closely related strains. Endemic in the North-Eastern region of Ukraine, genotype B3 was often imported to European countries. It is known that a large number of "named strains" are represented by this genotype. According to our data and literature, the measles virus, like all RNA-containing viruses, is highly mutagenic. We found a characteristic endemicity of certain strains of measles virus in the North-Eastern region of Ukraine. Conclusion. The most common strains are Gir Somath D8, Cambridg genotype D8 and aggressive Kabul genotype B3. Also, based on the analysis of genealogical trees, we can assume that Edmonston-ZagrebB3, MVsB3CaliforniaUSA, MVsB3PadovaITA, MVsB3LondonGBR genotype B3 and strain D8Kheda IND genotype D8 are endemic in Northeastern Ukraine. The data obtained by us are of great importance for studying the ways of transmission and improvement of measures of epidemiological surveillance of the disease and require further careful study. Keywords. variability,epidemically active strains, measles virus, circulating, North-Eastern region of Ukraine. DOI: 10.5281/zenodo.6634893